Differential segmental motion contribution of single- and two-level anterior cervical discectomy and fusion - Chien, Andy; Lai, Dar-Ming; Wang, Shwu-Fen; Cheng, Chih-Hsiu; Hsu, Wei-Li; Wang, Jaw-Lin (European spine journal, 2015)
Purpose To determine and compare the biomechanical effects of single- and two-level anterior cervical decompression and fusion (ACDF) on the re-distribution of the segmental contribution to total cervical range of motion (ROM) in a prospective longitudinal design. Methods Fifty-one patients undergoing either a single- or two-level ACDF due to cervical disc disease were recruited. Functional radiographs were taken preoperatively and then at 3, 6 and 12-month follow-ups. Global ROM of C2–C7, ROM of the treated functional spinal unit (FSU) and the superior and inferior segmental ROMs were then measured. The relative contribution from the FSU and each of the adjacent segments to total cervical ROM were compared pre- and post-operatively within and between the two groups at each of the time points. Results Single-level ACDF patients demonstrated a significantly greater total cervical ROM at 6 and 12 months compared with the two-level ACDF group ( p = 0.021 and 0.045, respectively). A significantly greater contribution from the FSU to the total ROM was found at 3 months in the two-level ACDF group ( p = 0.016), but the greater contribution shifted to the superior adjacent segment at 6 and 12 months ( p = 0.025 and 0.046). The two-level ACDF group did not demonstrate a significant difference at 3 months ( p = 0.087), but a significant increase in contribution was found at 6 and 12 months ( p < 0.01). Conclusions Single-level ACDF maintains and restores a more physiological re-distribution of segmental contribution of ROM compared with two-level ACDF, which required longer time to achieve stable FSU immobilization and coupled with significantly increased superior segment contribution.